DOP22 UC-related and segment-specific properties of patient-derived colonic organoids. (25th January 2019) - Suzuki, K; Shimizu, H; Kawai, M; Takahashi, J; Anzai, S; Kawamoto, A; Nagata, S; Hiraguri, Y; Yui, S; Tsuchiya, K; Nakamura, T; Ohtsuka, K; et al.
Abstract: Background: Colonic stem cells (CSCs) play indispensable roles in the maintenance and the regeneration of the colonic epithelium. It has been reported that the inflammatory environment of ulcerative colitis (UC) or Crohn's disease (CD) can modify gene expression and functions of colonocytes and/or CSCs. Organoids generated from those patients can maintain disease-modified or segment-specific properties of colonocytes and CSCs in vitro . However, to what extent the patient-derived organoids generated from different colonic segments exhibit disease-specific phenotypes remain uncertain. Methods: Colonic organoids were established by using endoscopic biopsy specimens taken from various colonic segments of UC, CD, and non-IBD patients. Colonic segment-specific gene expression was analysed by microarray analysis. CSC-specific gene expression was examined at the single-cell level by microfluid-based multiplex qPCR analysis. Proliferation/growth efficiency of patient-derived organoids were evaluated for up to 33 days by using 3D scanner-based quantification method (Sci Rep, 2012) and/or haemocytometer-based cell counting. Results: A total of 55 colonic organoids were established from UC or CD patients in remission, and also from non-IBD patients. Organoids established from different colonic segments of the same patient successfully identified candidate segment-specific genes of the ascending colon (15 genes), transverse colon (5 genes), Sigmoid colon (3 genes), and rectum (5 genes). Single-cell gene expression data of 12 representative ISC-marker genes including LGR5, MYC, SLC12A2, LRIG1, SMOC2 revealed similar, indistinguishable expression pattern in segment-matched organoids of UC and non-IBD patients. Proliferation/growth efficiency profile of non-IBD patient-derived organoids also showed equivalent level and pattern between those from the ascending colon and the rectum. However, in sharp contrast, proliferation/growth efficiency profile of UC patient-derived organoids clearly showed a segment-specific pattern, as those from the ascending colon generally exhibited over 2-fold higher proliferation efficiency compared with those from the rectum. Conclusions: Colonic organoids established from the ascending colon of UC patients maintain high in vitro proliferation potential compared to those established from the rectum. Results suggest colonic segment-specific modification of colonocyte function in UC patients, which may be further revealed by deeper gene expression analysis of our patient-derived organoid library.